Quantifying optimal growth policy - Volker Grossmann; Thomas M. Steger; Timo Trimborn (Center for Economic Studies and ifo Institute (CESifo), 2010)
The optimal mix of growth policies is determined within a comprehensive endogenous growth model. The analysis captures important elements of the tax-transfer system and accounts for transitional dynamics. Currently, for calculating corporate taxable income US firms are allowed to deduct approximately all of their capital and R&D costs from sales revenue. Our analysis suggests that this policy leads to severe underinvestment in both R&D and physical capital. We find that firms should be allowed to deduct between 2-2.5 times their R&D costs and about 1.5-1.7 times their capital costs. Implementing the optimal policy mix is likely to entail huge welfare gains.
Keywords: H20; O30; O40; 330; economic growth; endogenous technical change; optimal growth policy; tax-transfer system; transitional dynamics; Wachstumspolitik; Investitionspolitik; Forschungssubvention; Steuerbegünstigung; Körperschaftsteuer; Steuerwirkung; Optimales Wachstum; Endogener technischer Fortschritt; Theorie; USA